(untitled) (Ameghiniana, 2018)
The bioclastic accumulations produced during the Holocene transgression are recorded in the entire coastal zone of South America, and allow the correlation of different areas. In order to place information from taxonomy, taphonomic process and paleoecology in this context, the analyses of mollusk fauna from six different sites located in the coastal plain of Cabo Frio area, southeastern Brazil, were integrated with sea level and paleoenvironmental changes. The taxonomic analysis identified 42 species of mollusks, being 25 of Bivalvia Class, 15 of Gastropoda Class and 2 of Scaphoda Class. The taphonomic analysis demonstrated two types of assemblages, an autocthonous, formed in anoxic and hypersaline conditions, and an allochthonous, characterized by shallow marine environment. Radiocarbon dating revealed the ages between 6260 and 5819 cal. yr BP. Cluster analysis revealed four fauna associations: Anomalocardia brasiliana, Tivela mactroides, Neritina virginea / Olivella and Pitar fulminatus. The integration of mollusk associations and taphonomic signatures allowed distinguished two paleoenvironments: a marine restricted (6200—5950 cal. yrs BP) dominated by Anomalocardia brasiliana Association with low degree of abrasion and fragmentation, evidence of low-energy environment; and 2) nearshore nearshore (5950—5800 cal. yrs BP) dominated by Tivela mactroides, Neritina virginea / Olivella and Pitar fulminatus Associations with a high degree of fragmentation and disarticulation, denoting a high wave energy environment and marine currents.